Primary central nervous system vasculitis and its mimicking diseases: clinical features, outcome, comorbidities and diagnostic results : a case control study - Becker, Jana; Berlit, Peter (Clinical neurology and neurosurgery, 2017)
Objectives: To compare clinical features and outcome, imaging characteristics, biopsy results and laboratory findings in a cohort of 69 patients with suspected or diagnosed primary central nervous system vasculitis (PCNSV) in adults; to identify risk factors and predictive features for PCNSV. Patients and methods: We performed a case-control-study including 69 patients referred with suspected PCNSV from whom 25 were confirmed by predetermined diagnostic criteria based on biopsy (72%) or angiography (28%). Forty-four patients turned out to have 15 distinct other diagnoses. Clinical and diagnostic data were compared between PCNSV and Non-PCNSV cohorts. Results: Clinical presentation was not able to discriminate between PCNSV and its differential diagnoses. However, a worse clinical outcome was associated with PCNSV (p=0.005). Biopsy (p=0.004), contrast enhancement (p=0.000) or tumour-like mass lesion (p=0.008) in magnetic resonance imaging (MRI), intrathecal IgG increase (p=0.020), normal Duplex findings of cerebral arteries (p=0.022) and conventional angiography (p=0.010) were able to distinguish between the two cohorts. Conclusion: In a cohort of 69 patients with suspected PCNSV, a large number (64%) was misdiagnosed and partly received treatment, since mimicking diseases are very difficult to discriminate. Clinical presentation at manifestation does not help to differentiate PCNSV from its mimicking diseases. MRI and cerebrospinal fluid analysis are unlikely to be normal in PCNSV, though unspecific if pathological. Cerebral angiography and biopsy must complement other diagnostics when establishing the diagnosis in order to avoid misdiagnosis and mistreatment.